The Relationship of Knowledge With Community Stigma Towards Mental Disorders in The Region of Rt 01/Rw 14, Jatibening District, Pondok Gede Bekasi 2025 - Elfira Sri Futriani; Rosalia Rosalia; Puji Wijayanti (Universitas Pahlawan Tuanku Tambusai, 2026)
Background: Mental disorders remain a significant public health problem and are often accompanied by negative stigma within society. Stigma toward People with Mental Disorders (PMD) can hinder recovery processes, limit access to mental health services, and reduce social acceptance. One of the factors influencing stigma is the level of public knowledge regarding mental disorders. A preliminary study conducted in RT 01/RW 14 Jatibening Subdistrict indicated that community knowledge about mental disorders was still limited and negative stereotypes toward PMD were still prevalent. Objective: To determine the relationship between community knowledge and public stigma toward mental disorders in RT 01/RW 14 Jatibening Subdistrict, Pondok Gede – Bekasi in 2025.Methods: This study employed a quantitative research design with a cross-sectional approach. The population consisted of community members in RT 01/RW 14 Jatibening Subdistrict, with a total sample of 62 respondents calculated using the Slovin formula with a 10% margin of error. The sampling technique used was simple random sampling. Data were collected using structured questionnaires measuring knowledge and stigma (adapted from the Community Attitudes toward the Mentally Ill/CAMI scale). Data analysis was performed using univariate and bivariate analysis with the Chi-Square test at a significance level of α = 0.05 using SPSS version 26.Results: The majority of respondents had a moderate level of knowledge (32 respondents; 51.6%). Most respondents demonstrated a moderate level of stigma (31 respondents; 50.0%). The Chi-Square test showed a p-value of 0.000 (< 0.05), indicating a statistically significant relationship between knowledge level and public stigma toward mental disorders.Conclusion and Recommendations: There is a significant relationship between community knowledge and stigma toward mental disorders. Higher levels of knowledge are associated with lower levels of stigma. It is recommended that local health centers and regional authorities strengthen community-based mental health education programs to improve mental health literacy and reduce stigma toward individuals with mental disorders.